Manifestations Of School-Level Mediation Factors During Syllabus Implementation: A Case Of Localised Advanced Level Geography Syllabus - Dzimiri, Wonderful (Advances in Social Sciences Research Journal, 2018)
This article investigated manifestation of school-level factors mediating the implementation of the Zimbabwe localised Advanced level Geography syllabus introduced in 2002. Employing a concurrent triangulated strategy, the population entailed 19 high schools offering Advanced level Geography in the Gweru district comprising rural, high density, low density and mission high schools, 287 Advanced level Geography students, 103 former students, and 21 Geography teachers. Stratified random sampling of 12 (63%) schools ensured inclusion of school categories typical of Gweru high schools. 287 (88%) current students and 52 (50%) former students were selected as sample participants using stratified random sampling technique. 12 teachers were selected purposively. Questionnaires, lesson observations and structured interview techniques concurrently employed generated data for the study. Data were analysed using frequencies (numbers), and in some instances, with corresponding percentages. Major findings were that teachers did not cover all syllabus topics. Most teachers did not have detailed lesson plans and largely used the scheme-cum plan. Objectives were clearly stated and linked to syllabus goals. Lesson deliveries were teacher-centred and employed traditional as opposed to interactive, child-centred methods. Textbooks available were inadequate, outdated and of little relevance to the new syllabus. Mission and low density urban schools were better resources compared to rural and high density urban schools. The study recommends that, over and above staff-developing teachers on all syllabus topics, schools should provide relevant material resources and technology that enhance interactive methods where students can actively participate and gain ownership of their learning.